Capturing digital developments through qualitative inquiry. Issue 1 (11th April 2016) - Kyrillidou, Martha; Cook, Colleen; Lippincott, Sarah
Abstract : Purpose: – The purpose of this paper is to describe a model of digital library (DL) work that surfaced through the ARL Profiles 2010 and resonates current work underway by the large-scale DL projects like DPLA, SHARE, Hathitrust, Academic Preservation Trust, and Digital Preservation Network. Design/methodology/approach: – In total, 86 ARL members submitted institutional profiles that were analyzed using Atlas.ti and surfaced major themes that comprise the mission of research libraries including serving the public good, expanding their presence globally, setting standards for access and quality, needing to explore best practices, and being visible at the national and international levels. Findings: – The analysis of the narratives identified three key areas for DL developments: first, digitized special collections, second, acquiring digital content, and third, developing digital services (Figure 1). Specific examples and context are provided in the paper. Research limitations/implications: – The qualitative data collected from these profiles demonstrate that libraries are transforming their services to leverage digital technologies and meet the changing needs of their users. The approach was open ended and allowed libraries to celebrate their strengths and unique context. Some of the disadvantages of this approach include the amount of work both on behalf of the participating libraries as well as on behalf of the analysts and the difficulty of comparing libraries with one another. Originality/value: – This was the first time ARL attempted to describe research libraries using narrative descriptions. The approach complements the traditional ARL Statistics and offers a viable alternative in a future environment that is dominated by radical change. This qualitative approach deployed here is critical for describing DL developments as current large-scale digitization projects have extended the directions that were surfacing in these profiles and have major implications for the future of digital content and research. Future research in this area is strongly encouraged.